Professional Commitment Among Prospective Teachers: A Preparedness of Integrated Teacher Education Programme for a Developed Nation - Subhrajyoti, Trupti; Acharya, Amulya Kumar (Randwick International of Education and Linguistics Science Journal, 2025)
Teacher education has taken the responsibility to prepare 21st century fit teachers grounded in Indian values, languages and traditions as well as an updated package of advanced technological, pedagogical masterpiece where Professional commitment of prospective teachers is a crucial factor in the effectiveness of Integrated Teacher Education Programs (ITEP), particularly in the context of developing nation. Therefore, the researcher of the present study has tried to assess the professional commitment of the prospective teachers of this course and gauge the way forward for a developed nation. Researcher selected 50 final year prospective teachers from ITEP purposefully and resulted after suitable data collection techniques that professional commitment varied in case of gender dynamics and commitment to profession and commitment to society were difficult for female teacher trainees of ITEP. As nation strive for educational advancement, professional commitment in teacher education programs will prepare prospective teachers not only to meet the demands of their roles but also to contribute positively to the broader educational ecosystem. This preparedness is vital for fostering a skilled workforce capable of driving societal progress and achieving sustainable development goals.